The Impact of the Continuum of an Education Programme on Pre-service Teachers' Beliefs about English Language Education - Martina Siposova; Lucia Svabova (National Research University Higher School of Economics, 2022)
Research background: Teachers' beliefs play an important role in the way they teach and meet their students' needs. Researching pre-established pre-service teachers' beliefs gives evidence that they might impede pre-service teachers' compliance with pre-service education. Gap in knowledge and Purpose of the study: Many studies have produced contradictory findings in terms of prospective change in pre-established pre-service teachers' beliefs caused by the impact of pre-service education study programmes. Therefore, this study addresses the gap by enriching this field with research findings reinforcing the potential impact of the study programme on changes in pre-service teachers' beliefs on effective English language teaching and learning expressed across different years of the study programme. Methods: The study uses the results of questionnaires completed by 99 randomly selected pre-service teachers enrolled in an English language teaching study programme provided by the Faculty of Education, Comenius University in Bratislava, Slovakia. In addition, the study participants' database was expanded using bootstrapping to enhance the results obtained by applying statistical methods. Findings and Value added: The results showed statistically significant differences among different years of the study programme within the continuum of their English language teacher education thus indicating the potential impact of the programme. The impact of the study programme led to pre-service teachers' raised awareness and some modifications in their pre-established beliefs based on the learnt and acquired knowledge and gained practical teaching experiences during the practicums in higher grades of the study. The findings suggest that teacher educators and policymakers should be aware of pre-service teachers' beliefs when adopting new strategies for reconceptualising and/ or modifying language teacher education programmes.